Efektivitas Metode Pembelajaran Slim-N-Bil terhadap Hasil Belajar Matematika - Indra Martha Rusmana; Nurhayati Nurhayati (Universitas Indraprasta PGRI, 2015)
Mathematics achievement is a reflection of learner achievement in learning mathematics, if the concept is given to students has been well received, the results obtained will be a good learning. Mathematical concepts can be given by various methods so that learners are able to understand the material provided by the teacher, one math learning methods are SLIM-n-BIL. The purpose of this study is to determine the effect and the effectiveness of SLIM-n-BIL learning methods on mathematics achievement. The method used a quasi-experimental methods are implemented in junior Mahardika with data retrieval via multiple choice questions. Hypothesis testing is performed using SPSS 17.0 software for windows at significance level of 0.05. The conclusions are: there is an effect of using SLIM-n-BIL in understanding mathematical concepts and the method SLIM-n-BIL effective against students’ mathematics achievement because the effect size obtained value of 0,685.